2021
DOI: 10.1039/d0ta12458c
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic effects of electrochemical oxidation of Spiro-OMeTAD and Li+ ion migration for improving the performance of n–i–p type perovskite solar cells

Abstract: n-i-p Type perovskite solar cell generally requires air oxidation of Spiro-OMeTAD layer to achieve high power conversion efficiency (PCE). However, the detailed oxidation mechanism is still not fully understood. In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 47 publications
4
67
0
Order By: Relevance
“…In this work, both pre‐ and post‐oxidation of the Spiro‐OMeTAD layers were performed to improve the conductivity of the Spiro‐OMeTAD layer and the consequent solar cell performance. [ 50 ] Although these cells were oxidized in air under similar conditions, the variation of device performance indicated that oxidization degree of the Spiro‐OMeTAD films was not well controlled and the properties of Spiro‐OMeTAD varied from batch to batch. In other words, the conductivity as well as the surface property of the Spiro‐OMeTAD layer is different from each other after oxidation, which influences the silver electrode on it and leads to a large variation of the failure time during aging (Table S1, Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In this work, both pre‐ and post‐oxidation of the Spiro‐OMeTAD layers were performed to improve the conductivity of the Spiro‐OMeTAD layer and the consequent solar cell performance. [ 50 ] Although these cells were oxidized in air under similar conditions, the variation of device performance indicated that oxidization degree of the Spiro‐OMeTAD films was not well controlled and the properties of Spiro‐OMeTAD varied from batch to batch. In other words, the conductivity as well as the surface property of the Spiro‐OMeTAD layer is different from each other after oxidation, which influences the silver electrode on it and leads to a large variation of the failure time during aging (Table S1, Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The same trend of Li + ion distribution had been reported in previous literature. 44,45 For the control device, a much higher Li + ion signal at the SnO 2 layer than that at the HTL can be found, suggesting a rather serious Li + ion migration. In sharp contrast, Li + ions primarily located within the target HTL and a relatively small portion of Li + ions are diffused out and detected at the SnO 2 layer, indicating the ion migration has been greatly suppressed.…”
Section: Resultsmentioning
confidence: 99%
“…The same trend of Li + ‐ion distribution had been reported in previous reports in the literature. [ 46,47 ] For the control device, a much higher Li + ‐ion signal at the SnO 2 layer than that at the HTL can be found, suggesting a rather serious Li + ‐ion migration. In sharp contrast, Li + ions primarily located within the target HTL and a relatively small portion of Li + ions are diffused out and detected at the SnO 2 layer, indicating the ion migration has been greatly suppressed.…”
Section: Resultsmentioning
confidence: 99%